Efficacy and toxicity of whole brain radiotherapy in patients with multiple cerebral metastases from malignant melanoma - Hauswald, Henrik; Dittmar, Jan Oliver; Habermehl, Daniel; Rieken, Stefan; Sterzing, Florian; Debus, Jürgen; Combs, Stephanie (Radiation oncology, 2012)
Background: To retrospectively access outcome and toxicity of whole brain radiotherapy (WBRT) in patients with multiple brain metastases (BM) from malignant melanoma (MM). Patients and methods: Results of 87 patients (median age 58 years; 35 female, 52 male) treated by WBRT for BM of MM between 2000 and 2011 were reviewed. Total dose applied was either 30 Gy in 10 fractions (n = 56) or 40 Gy in 20 fractions (n = 31). All but 9 patients suffered from extra-cerebral metastases. Prior surgical resection of BM was performed in 18 patients, salvage stereotactic radiosurgery in 13 patients. Results: Mean follow-up was 8 months (range, 0-57 months), the 6- and 12-months overall-(OS) survival rates were 29.2% and 16.5%, respectively. The median OS was 3.5 months. In cerebral follow-up imaging 6 (11) patients showed a complete (partial) remission, while 11 (17) patients had stable disease (intra-cerebral tumor progression). In comparison of total dose, the group treated with 40 Gy in 20 fractions achieved a significant longer OS (p = 0.003, median 3.1 vs. 5.6 months). Furthermore, DS-GPA score (p < 0.001) as well as RPA class (p < 0.001) influenced significantly on OS and patients had a significantly longer OS after surgical resection (p = 0.001, median 3.0 vs. 5.8 months, multivariate p = 0.007). Having extra-cerebral metastases didn't significantly impact on OS (p = 0.21). Conclusion: Treatment of BM from MM with WBRT is tolerated well and some remissions of BM could be achieved. An advantage for higher treatment total doses was seen. However, outcome is non-satisfying, and further improvements in treatment of BM from MM are warranted.
Gesehen am 16.10.2018